Farmer Perceptions of Wildlife Damage to Row Crops in North Florida - Holly K. Ober; Gerald R. Edmondson; William M. Giuliano; David L. Wright; John Atkins; Andy Andreasen; Shep Eubanks; Libbie Johnson; Charles Brasher; Greg Hicks (EDIS)
How can we determine the just how much of an impact wildlife damage has on growers? This 4-page fact sheet presents the results of a survey of a sample of growers across the state. Written by Holly K. Ober, Gerald R. Edmondson, William M. Giuliano, David L. Wright, John Atkins, Andy Andreasen, Shep Eubanks, Libbie Johnson, Charles Brasher, and Greg Hicks, and published by the UF Department of Wildlife Ecology and Conservation, July 2011.